The effect of The effect of the number of employees, profitability, business growth on the risk management system: in the Matam Clinic - Dedy Triyono; Vip Paramarta; Ayu Laili Rahmiyati (LP2M IAIN Palopo, 2026)
Study This aim analyze influence amount employees , profitability , and growth business to system management risk at the M Eye Clinic in Blitar City . Research This use approach descriptive quantitative supported by qualitative data from interview For enrich interpretation results analysis . Test results hypothesis show that amount employees (X1), profitability (X2), and growth effort (X3) has an effect positive and significant to system management risk (Y). Significance value of each variable is 0.019 for amount employees , 0.046 for profitability , and 0.047 for growth business , all of which more small from 0.05. With thus , thirdly hypothesis study accepted in a way partial , affirmative that variables the own contribution significant in strengthen system management risks at M Eye Clinic. Keywords : Number of Employees, Profitability , Business Growth , System Management Risk , M Eye Clinic